(untitled) (Veterinary Science, 2017)
The province of La Pampa (Argentina) is characterized by high concentrations of arsenic and fluorine in groundwater. In this work, the concentration of fluorine and arsenic in public potable water from General Pico and its evolution were determined. The average concentration of both arsenic (0.059 mg/l) and fluorine (2,339 mg/l) in the public tap water during the period 2007-2013 exceeded those figures allowed for human consumption by the Argentine Food Code and the World Health Organization, whose maximum acceptable figures are 0.01 mg/l for arsenic and 1.2 mg /l for fluoride. The arsenic concentration in the public potable water tended to decrease when rainfall increased, while the fluoride concentration was independent of the level of precipitations. People exposed to high concentrations of arsenic tend to be also exposed to high concentrations of fluoride